PEMBUATAN ALAT PENYEMAI BENIH PADI MEKANIS SISTEM DAPOG (The Making of Mechanical Dapog System Rice Seeding Equipment) - Lourent Sirait; Taufik Rizaldi; Saipul Bahri Daulay (Jurnal Rekayasa Pangan dan Pertanian, 2018)
ABSTRACT Various technologies have been developed to increase production, superior varieties of rice and also technology of rice cultivation. The making of mechanical  dapog system seeding rice equipment is a way to improve equipment the work that has the function of rice seed to grow was superior rice seedlings using box applications. The objective of this research was to test the mechanical  dapog system seeding rice equipment and to support the planting of rice seedlings mechanically, using rice transplanter and accelerate the process of seeds equipment planting. This research used linear method to know the analysis of a tool. The parameters observed were the effective capacity of the tool, the percentage of damaged seeds, the need for electric power and the percentage of seeds grown. The results showed that the average effective capacity of the mechanical  seed rice equipment in a dapog system was 315 boxes / hour. Percentage of damaged seed was 5.17%. The power requirement of the appliance was 247.5 watts. the percentage of seeds that grew was 94.83%. The cost of principal and BEP for the first year until the fifth year was 153.10 / box and 5,593,46 square / year, while the IRR was 50.07%. Based on the results of this study it can be stated that the equipment feasible. Keywords: equipment  making, seeding, rice seed and dapog system. ABSTRAK Berbagai teknologi telah dikembangkan untuk dapat meningkatkan produksi, varietas unggul padi dan juga teknologi budidaya tanaman padi. Pembuatan alat penyemai benih padi mekanis sistem dapog merupakan suatu cara yang dilakukan untuk peningkatan kerja alat yang memiliki fungsi menyemaikan benih padi agar dapat tumbuh menjadi bibit padi unggul dengan menggunakan aplikasi kotak. Penelitian ini bertujuan untuk menguji alat penyemai benih padi mekanis sistem dapog serta mendukung penanaman bibit padi secara mekanis yang menggunakan alat rice transplanter dan mempercepat proses penanaman bibit. Penelitian ini menggunakan metode linear untuk mengetahui analisis suatu alat. Parameter yang diamati adalah kapasitas efektif alat, persentase benih yang rusak, kebutuhan daya listrik dan persentasi benih yang tumbuh. Hasil penelitian menunjukkan bahwa kapasitas efektif rata-rata pada alat penyemai benih padi mekanis sistem dapog adalah 315 kotak/jam. Persentase benih yang rusak 5,17%. Kebutuhan daya listrik alat sebesar 247,5 watt. persentasi benih yang tumbuh94,83%. Biaya pokok dan BEP untuk tahun pertama sampai tahun kelima sebesar 153,10/kotak dan 5.593,46 kotak/tahun, sedangkan IRR sebesar 50,07%. Berdasarkan hasil penelitian ini dapat dinyatakan bahwa alat layak untuk diusahakan.   Kata kunci: Pembuatan alat, penyemaian, benih padi dan sistem dapog.